Challenges facing seaborne cargo operations in Nigeria: a case study of Lagos Port Complex - Stephen, Mobolaji (Annals of Spiru Haret University. Economic Series, 2021)
This paper aims to look into the challenges confronting seaborne cargo operations in Nigeria, using Lagos Port Complex (LPC) as a case study. The research adopted expository research design. Lagos Port Complex was the sample frame, and 230 questionnaires was administered using purposive sampling technique. Descriptive statistics was used for the analysis. Tables and the centre tendency to ascertain the opinion of the respondents were used. The results shows that the challenges confronting the maritime operation in Nigeria include the fact that foreign vessels berth more in LPC; import cost are very high; lack of export makes ships to frequently sail back on ballast; and finally, foreign dominance in Nigeria territorial waters. The respondents seems more indifferent about the adequacy or inadequacy port infrastructures in handling the cargoes at the port, with regards to mechanized as well as port-system upgrade to international standard. Respondents were also indifferent about foreigners manning the ships (meaning that if the CABOTAGE Act had not failed in its essence that should not have been a problem that needs attention or be spoken about after fifteen years of enacting the Act). It can be said that the CABOTAGE Act have not actualize its essence. These challenges confronting the maritime operations in Nigeria should have been addressed through the CABOTAGE Act.